Teatro científico: uma estratégia interdisciplinar de integração de conteúdos de ciência, tecnologia e sociedade. - Bezerra, Roseana da Silva (2018)
In the case of education, it is believed that the search for new methodologies that contribute to teaching and its quality is always pertinent. Faced with the possible scenario in which there are students who are not motivated to learn science, it is possible to see an even greater need to innovate in teaching by bringing methodologies that awaken in the student the curiosity to learn, making him also responsible for your. Thus, it is perceived today use of several teaching methodologies and tools that promote this learning and stimulus. Among these methodologies is the Scientific Theater (TC), which can still be considered a new methodology in this sense, but it is believed be very effective in what it promises, which is teach science and allow its dissemination in a playful way and attractive way to eyes of those who participate form active and as televiewer. The aim of this dissertation research was to analyze the use of CT as an interdisciplinary tool in science teaching, bringing approaches to science, technology and society (CTS) contents in a theatrical scientific project at the Federal Institute of Education, Science and Technology of Rio Grande do Norte (IFRN), highlighting the importance of this tool in the teaching-learning process.For this, this research was carried out in three stages: initially, a state of knowledge, which sought to identify and better know how the TC universe has been given in the production of master's dissertations in Brazil over a period of 10 years; posteriorly, a research that sought to know the existence of TC groups in the city of Mossoró / RN, as well as to conduct semi-structured interviews with teachers of these TC groups; and, finally, an intervention research, based on the creation of a TC group in high school the from IFRN also in the city of Mossoró, which included the elaboration of a theatrical script with CTS approaches and a focus group (GF) interview that aimed to know, in the view of the students, how this experience was given. At the end of this research, it was noticed that although the state of knowledge has presented few master's dissertations and publications cited in these dissertations that approach TC in high school in a period of ten years, we have been able to confirm that CT is a tool that contributes a lot in the teaching-learning process and quality of teaching. The TC groups found in the city of Mossoró - RN showed positive actions in the teaching quality of the student who works in the respective theater groups, proposing the formation of a critical and thinking student about science teaching. Despite this, teachers working in these groups reported that they find it difficult to receive support from other school teachers in interdisciplinary work. Regarding the assembly of the TC group in the IFRN, it was observed that the students were very motivated regarding the use of the TC as a teaching tool, and that the same ones reported that the activity was productive in learning the contents of CTS, confirming once again its efficiency in the direction of learning